2020
DOI: 10.1186/s12870-020-02670-3
|View full text |Cite
|
Sign up to set email alerts
|

Selection and validation of reference genes for measuring gene expression in Toona ciliata under different experimental conditions by quantitative real-time PCR analysis

Abstract: Background Before studying gene expression of different organisms, it is important to determine the best reference gene. At present, the most accurate method of detecting gene expression is quantitative real-time PCR (RT-qPCR). With this method, reference genes that are stable in different biological systems and under different conditions can be obtained. Toona ciliata Roem (T. ciliata). is a valuable and fast-growing timber specie. In this study, 20 reference genes were identified using RT-qPC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…GeNorm and NormFinder calculate the gene expression stability and then sort the candiate reference genes by SV, whereas BestKeeper calculates the results based on the SD and CV of the Ct value [ 24 26 ]. Because of the various algorithms employed in the three software packages, they have distinct rankings for identical experimental datasets [ 12 ], despite the fact that the analysis outcomes of NormFinder and GeNorm in this study hardly changed. For instance, the analysis of BestKeeper and GeNorm suggested that PP2A and UBC5 were the two optimal reference genes in drought-treated leaves of Q .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GeNorm and NormFinder calculate the gene expression stability and then sort the candiate reference genes by SV, whereas BestKeeper calculates the results based on the SD and CV of the Ct value [ 24 26 ]. Because of the various algorithms employed in the three software packages, they have distinct rankings for identical experimental datasets [ 12 ], despite the fact that the analysis outcomes of NormFinder and GeNorm in this study hardly changed. For instance, the analysis of BestKeeper and GeNorm suggested that PP2A and UBC5 were the two optimal reference genes in drought-treated leaves of Q .…”
Section: Discussionmentioning
confidence: 99%
“…RefFinder was applied to integrate and create comprehensive candidate reference gene rankings in accordance with the geometric average of each gene weight counted using each program [ 35 ]. Many researchers also employ RankAggreg to count the ultimate ranking [ 8 , 11 , 12 ]. RankAggreg applies a genetic algorithm or cross-entropy Monte Carlo algorithm to calculate the ranking of reference genes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are usually used to calibrate qPCR results, so a stable reference gene is needed for qPCR. Nevertheless, several studies indicated that the expression levels of these traditional housekeeping genes varied widely in various experimental conditions among many species [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Consequently, selecting a stable and suitable reference gene has become increasingly crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of an “ideal” reference gene will not vary with treatment or physiological state in the tissue studied. However, several studies have shown that no perfect reference gene exists because the reference gene can be influenced by species, different tissues, developmental stages and diseases, etc [ 2 , 17 , 29 ]. Consequently, it is becoming an essential component of qPCR to systematically evaluate common and novel reference genes derived from genomewide analyses so as to improve the reliability of research results.…”
mentioning
confidence: 99%